Silane-terminated polyether prepared from ethoxyquinoline polymer as well as preparation method and application of silane-terminated polyether

By amine-dissolving and polymerizing ethoxyquinoline polymer with propylene oxide, and combining with organosiloxane, silane-capped polyether was prepared, which solved the problem of resource utilization of heavy-component polymers with ethoxyquinoline distillation, and achieved the preparation and application of high-performance silane-capped polyether.

CN119798641APending Publication Date: 2025-04-11JIANGSU LITIAN TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510006243.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-27
Filing Date
2025-01-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize ethoxyquinoline to distillate the recombinant polymer, resulting in waste of resources.

Method used

By amine-decomposing the ethoxyquinoline polymer with propylene oxide, an amine alcohol was prepared, and then polymerized with propylene oxide to form ethoxyquinoline polyether polyol, and finally reacting with isocyanate-containing organosiloxane to prepare silane-capped polyether.

Benefits of technology

The resource utilization of the heavy-component polymer of ethoxyquinoline distillation is realized. The prepared silane-capped polyether has the advantages of rapid curing, high strength, strong adhesion, moisture resistance, low odor and environmental protection, and is suitable for glass glue, sealant, nail-free glue and ceramic tile adhesive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005226951260000032
    Figure BDA0005226951260000032
  • Figure BDA0005226951260000041
    Figure BDA0005226951260000041
  • Figure BDA0005226951260000051
    Figure BDA0005226951260000051
Patent Text Reader

Abstract

The invention discloses silane-terminated polyether prepared from an ethoxyquin polymer, which is prepared by the following method: carrying out aminolysis reaction on the ethoxyquin polymer and epoxypropane to prepare amino alcohol; taking amino alcohol as an initiator, and carrying out polymerization reaction on the amino alcohol and epoxypropane to prepare ethyoxyl quinoline polyether polyol; the ethyoxyl quinoline polyether polyol and organic siloxane containing an isocyanate group are subjected to a reaction, and the silane-terminated polyether is prepared. According to the method, resource utilization of the ethoxyquin distillation still residues is realized. Due to the introduction of a rigid nitrogen-containing heteroatom quinoline ring structure and a polar carbamate structure, the silane-terminated polyether prepared from the ethoxyquinoline polymer has the advantages of high curing speed, high strength after curing, strong adhesion, moisture resistance, low odor, environment friendliness, no solvent and the like, can be used for glass cement, sealant, nail-free glue, ceramic tile adhesive and the like, and has wide application prospects. The method can be widely applied to building industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials and relates to a silane-terminated polyether prepared by using an ethoxyquinoline polymer and a preparation method and application thereof. Background Art

[0002] Ethoxyquinoline is a very economical and effective antioxidant, which is widely used. It is not only used for food preservation, but also can slow down rubber aging, inhibit vitamin oxidation, and prevent fruit skin from discoloration due to oxidation. However, for every ton of ethoxyquinoline crude oil produced, about 0.25 tons of distilled heavy polymers will be produced. The resource utilization of heavy polymers has always been a technical problem that has plagued the development of the industry.

[0003] Polymers whose main chains contain ether bonds (—R—O—R—) and whose end groups or side groups contain more than 2 hydroxyl groups (—OH) are collectively referred to as polyether polyols. Polyether polyols are synthesized by homopolymerization or copolymerization of polyhydroxy or polyamine compounds as initiators with oxidized olefins in the presence of catalysts. Polyether polyols are colorless to brown viscous liquids at room temperature, usually soluble in aromatic hydrocarbons, halogenated hydrocarbons, alcohols, ketones, and hygroscopic. Polyether polyols are commonly used in the manufacture of general-purpose polyurethane foams, adhesives, elastomers, etc., and are widely used. Special polyether polyols are also used as defoamers, surfactants, etc.

[0004] Silane-terminated polyether (STP-E) is mainly formed by the end-capping reaction of a difunctional or trifunctional siloxane compound containing an isocyanate group (-NCO) and a polyether prepolymer containing a terminal -OH group. It is a silane cross-linked organic polymer that combines the excellent properties of silicone and polyurethane. The main chain of the silane-terminated polyether is a macromolecular polyether structure, which brings good flexibility, impact resistance, deformation and displacement resistance, ductility and hydrolysis resistance to the base polymer. The two ends of the silane-terminated polyether contain ≥2 hydrolyzable siloxane groups. After contact with air, hydrolysis and condensation form Si-O-Si bonds, giving the silane-terminated polyether excellent water resistance, weather resistance, aging resistance and other properties.

[0005] Silane-terminated polyethers can be formulated into adhesives with the following properties: high elasticity comparable to silicone, good paintability, fast curing and high mechanical strength. These properties were previously thought to be achievable only with polyurethane. Therefore, silane-terminated polyethers are widely used. Today, the adhesive industry is facing conflicting needs, hoping that raw materials can meet strict environmental regulations while maintaining their high performance. Therefore, the research and development of silane-terminated polyethers is increasingly valued by technicians.

[0006] Since silane-terminated polyethers have excellent properties, if the application technology of silane-terminated polyethers can be combined with the heavy components of ethoxyquinoline distillation to achieve the resource utilization of ethoxyquinoline distillation heavy components polymers, then the technical problems that have been plaguing the development of the industry will find a feasible solution. Summary of the invention

[0007] The object of the present invention is to provide a silane-terminated polyether prepared from ethoxyquinoline polymer in view of the above-mentioned deficiencies in the prior art.

[0008] The purpose of the present invention can be achieved through the following technical solutions:

[0009] A silane-terminated polyether prepared from an ethoxyquinoline polymer is prepared by the following method: an ethoxyquinoline polymer is subjected to an aminolysis reaction with propylene oxide to prepare an amino alcohol; the amino alcohol is used as an initiator to undergo a polymerization reaction with propylene oxide to prepare an ethoxyquinoline polyether polyol; and the ethoxyquinoline polyether polyol is reacted with an isocyanate-containing organic siloxane to prepare a silane-terminated polyether.

[0010] Preferably, the silane-terminated polyether prepared from the ethoxyquinoline polymer is prepared by the following method: using butyl acetate or xylene as a reaction solvent, under the action of a catalyst, the ethoxyquinoline polymer undergoes an aminolysis reaction with propylene oxide to prepare an amino alcohol; using butyl acetate or xylene as a reaction solvent and the amino alcohol as an initiator, under the action of a catalyst, the amino alcohol and propylene oxide undergo a polymerization reaction to prepare an ethoxyquinoline polyether polyol; under the action of a catalyst, the ethoxyquinoline polyether polyol reacts with an isocyanate-containing organosiloxane to prepare a silane-terminated polyether.

[0011] Ethoxyquinoline is generally prepared by condensing p-aminophenyl ether with acetone in the presence of p-toluenesulfonic acid as a catalyst, using toluene as the reaction solvent. After the reaction is completed, Na 2 CO 3 The aqueous solution is allowed to stand for stratification, and the upper organic layer is taken. The organic layer is put into a distillation kettle for distillation, and toluene, a fraction 1 with an ethoxyquinoline content of less than 78%, a fraction 2 with an ethoxyquinoline content of 78% or less and less than 88% (the distillation temperature is 190±5° C., and the vacuum degree is -0.096MPa±0.001MPa), and a finished product with an ethoxyquinoline content of 88% or less (the distillation temperature is 190±5° C., and the vacuum degree is -0.096MPa±0.001MPa) are sequentially distilled out, and an ethoxyquinoline distillation kettle residue is obtained in a distillation tower.

[0012] The ethoxyquinoline polymer is obtained by extraction using the residue of ethoxyquinoline distillation kettle as raw material and one selected from xylene or butyl acetate as extraction solvent.

[0013] Preferably, the ethoxyquinoline polymer is prepared by the following method: mixing the ethoxyquinoline distillation kettle residue with an organic solvent selected from butyl acetate or xylene, stirring and heating to 50-100° C., dissolving at a temperature of 50-100° C. for 1-3 hours, cooling after uniform dissolution, and filtering to obtain an ethoxyquinoline polymer solution.

[0014] More preferably, the ethoxyquinoline polymer is prepared by the following method: adding the ethoxyquinoline distillation kettle residue and an organic solvent selected from butyl acetate or xylene into a dissolution kettle, stirring and heating to 60-90° C., dissolving at a temperature of 60-90° C. for 1-2 hours, cooling after uniform dissolution, filtering, and obtaining an ethoxyquinoline polymer solution.

[0015] The xylene can be various isomers of xylene or a combination thereof, and the most commonly used is industrial grade mixed xylene.

[0016] Preferably, the mixture is cooled to 40°C and filtered.

[0017] The filtration adopts filter paper with a pore size of 20 microns.

[0018] Another object of the present invention is to provide a method for preparing a silane-terminated polyether prepared from the ethoxyquinoline polymer, comprising:

[0019] Step (1), pretreatment of ethoxyquinoline still residue: mixing an organic solvent selected from butyl acetate or xylene with the ethoxyquinoline still residue, stirring and heating to 50-100° C., dissolving at 50-100° C. for 1-3 hours, cooling after uniform dissolution, filtering, filtering out black solid particles formed by high-temperature carbonization of organic matter, and obtaining an ethoxyquinoline polymer solution;

[0020] Step (2), using one selected from butyl acetate or xylene as a reaction solvent, in the presence of a catalyst, the ethoxyquinoline polymer and propylene oxide undergo an aminolysis reaction to prepare an amino alcohol;

[0021] Step (3), using one selected from butyl acetate or xylene as a reaction solvent and the amino alcohol prepared in step (2) as an initiator, in the presence of a catalyst, the amino alcohol and propylene oxide undergo a polymerization reaction to prepare an ethoxyquinoline polyether polyol;

[0022] Step (4), in the presence of a catalyst, the ethoxyquinoline polyether polyol prepared in step (3) reacts with an isocyanate-containing organosiloxane, and the terminal hydroxyl group of the ethoxyquinoline polyether polyol reacts with the isocyanate group of the isocyanate-containing organosiloxane to introduce silane, thereby preparing a silane-terminated polyether.

[0023] In step (1), the mass ratio of the butyl acetate or xylene to the ethoxyquinoline distillation kettle residue is 1:0.5 to 1:2.0, preferably 1:1.0 to 1:1.6.

[0024] The theoretical amine value of ethoxyquinoline is 258 mgKOH / g.

[0025] The amine value of the ethoxyquinoline polymer solution is usually 80 to 110 mgKOH / g.

[0026] In step (2), represents ethoxyquinoline polymer, ethoxyquinoline polymer and propylene oxide undergo aminolysis reaction to obtain an amino alcohol with a structure as shown in formula I, and the synthesis route is as follows:

[0027]

[0028] The mass ratio of the ethoxyquinoline polymer solution to propylene oxide (56.1×1000 / Av): [58.08×(1.0~1.1)]; wherein 56.1 is the relative molecular weight of KOH, Av is the amine value measured by the ethoxyquinoline polymer solution, and 58.08 is the relative molecular weight of propylene oxide.

[0029] The catalyst is one or two or more of trifluoromethanesulfonates such as lanthanum trifluoromethanesulfonate, neodymium trifluoromethanesulfonate, erbium trifluoromethanesulfonate, ytterbium trifluoromethanesulfonate, scandium trifluoromethanesulfonate, cerium trifluoromethanesulfonate, stannous trifluoromethanesulfonate, bismuth trifluoromethanesulfonate, etc., and the mixture is preferably one or two or more of lanthanum trifluoromethanesulfonate, ytterbium trifluoromethanesulfonate, and scandium trifluoromethanesulfonate.

[0030] The dosage of the catalyst is 0.1wt% to 1wt% of the total mass of the ethoxyquinoline polymer solution and propylene oxide.

[0031] The temperature of the aminolysis reaction is 80°C to 120°C, the pressure is 0.1 to 0.4 MPa, and the end point of the reaction is when the pressure of the reaction system drops to a constant level. Generally, the time of the aminolysis reaction is 1 to 8 hours, when the pressure in the kettle drops to a constant level.

[0032] Specifically, the amino alcohol is prepared by the following method: in a pressure reactor, under the action of a catalyst, the ethoxyquinoline polymer solution prepared in step (1) is reacted with propylene oxide at a temperature of 80°C to 120°C and a pressure of 0.1 to 0.4 MPa until the pressure in the reactor drops to a constant level, and then cooled to below 50°C to obtain the amino alcohol.

[0033] Under the reaction conditions of the present invention, the epoxy group of propylene oxide is ring-opened and reacts with the secondary amine group of the ethoxyquinoline polymer to undergo addition reaction. When the pressure of the reaction system drops to a constant value, that is, the absorption of propylene oxide is completed, the reaction is considered to be finished.

[0034] In step (3), the amino alcohol with a structure as shown in formula I undergoes polymerization reaction with propylene oxide to obtain an ethoxyquinoline polyether polyol with a structure as shown in formula II. The synthesis route is as follows:

[0035]

[0036] The amount of amino alcohol is calculated based on the ethoxyquinoline polymer solution, and the mass ratio of the ethoxyquinoline polymer solution to propylene oxide is (56.1×1000 / Av):[58.08×(1.0~50)], preferably (56.1×1000 / Av):[58.08×(3~40)], and more preferably (56.1×1000 / Av):[58.08×(3~6)]; wherein 56.1 is the relative molecular weight of KOH, Av is the amine value measured by the ethoxyquinoline polymer solution, and 58.08 is the relative molecular weight of propylene oxide. The amount of propylene oxide used in step (3) does not include the amount of propylene oxide used in step (2).

[0037] The catalyst is one of sodium formate, potassium formate, sodium benzoate and potassium benzoate or a mixture of two or more of them in any proportion; the amount of the catalyst is 1wt% to 5wt% of the total mass of the amino alcohol and propylene oxide.

[0038] The polymerization temperature is 100°C to 165°C, preferably 140°C to 155°C, the polymerization pressure is 0.1 to 0.6 MPa, preferably 0.1 to 0.4 MPa, and the polymerization time is 1 to 8 hours, preferably 3 to 7 hours. Generally, the end point of the polymerization reaction is when the pressure of the reaction system drops to a constant level.

[0039] Specifically, the ethoxyquinoline polyether polyol is prepared by the following method: in a pressure reactor, one selected from butyl acetate or xylene is used as a reaction solvent, under the action of a catalyst, an amino alcohol and propylene oxide undergo a polymerization reaction, until the pressure in the reactor drops to a constant, the temperature is lowered to 80° C., and reduced pressure distillation is started to recover the organic solvent to 120° C., the vacuum degree is -0.098Mpa, and the temperature is 120° C., and no solvent is distilled out for 10 minutes, the distillation is terminated, the temperature is lowered to 60° C., activated white clay is added and stirred for 30 minutes, and cyclic pressure filtration is performed until it is clear and transparent to obtain the ethoxyquinoline polyether polyol.

[0040] More specifically, the ethoxyquinoline polyether polyol is prepared by the following method: after the reaction in step (2) is completed, when the reaction liquid drops to ≤50°C, a catalyst is added, and then the temperature is raised to a set reaction temperature, and propylene oxide is continuously and slowly added dropwise to carry out a polymerization reaction until the pressure in the kettle drops to a constant level, the temperature is lowered to 80°C, and reduced pressure distillation is started to recover the organic solvent to 120°C. At a vacuum degree of -0.098MPa and a temperature of 120°C, no solvent is distilled out for 10 minutes, the distillation is terminated, the temperature is lowered to 60°C, activated clay is added and stirred for 30 minutes, and cyclic pressure filtration is carried out until it is clear and transparent to obtain the ethoxyquinoline polyether polyol.

[0041] In step (4), the mass ratio of the ethoxyquinoline polyether polyol to the isocyanate-containing organosiloxane is (56.1×1000 / V OH ):[(0.5~1.0)×M], preferably (56.1×1000 / V OH ):[(0.8~1.0)×M]; where 56.1 is the relative molecular weight of KOH, V OH It is the hydroxyl value measured for ethoxyquinoline polyether polyol. The hydroxyl value of ethoxyquinoline polyether polyol is measured according to the national standard “GB / T 12008.3-2009 Plastic polyether polyol Part 3: Determination of hydroxyl value”. M is the relative molecular weight of the organosiloxane containing isocyanate group.

[0042] The organosiloxane is 3-isocyanate propyl trimethoxy silane (CAS No: 15396-00-6, relative molecular weight 205.28) or 3-isocyanate propyl triethoxy silane (CAS No: 24801-88-5, relative molecular weight 247.36), preferably 3-isocyanate propyl trimethoxy silane.

[0043] The catalyst is dibutyltin dilaurate; the amount of the catalyst used is 100 to 3000 ppm of the total mass of the ethoxyquinoline polyether polyol and the isocyanate-containing organosiloxane, preferably 100 to 1000 ppm.

[0044] The reaction temperature is 50°C to 95°C, preferably 60°C to 85°C, and the reaction time is 1 to 6 hours.

[0045] Specifically, the silane-terminated polyether is prepared by the following method: an isocyanate-containing organosiloxane and a catalyst are mixed, the temperature is raised to 60°C with stirring, and ethoxyquinoline polyether polyol is added dropwise through a constant pressure dropping funnel. During the addition, the temperature is controlled at 60-65°C, and the addition is completed within about 2 hours. The temperature is slowly raised to 80-85°C, and the reaction is kept warm for 3-5 hours. When the residual -NCO content of the system is ≤0.1%, the mixture is cooled to 60°C and filtered to obtain the silane-terminated polyether.

[0046] During the reaction, the hydroxyl group of the ethoxyquinoline polyether polyol reacts with the isocyanate group (-NCO) of the isocyanate group-containing organosiloxane to form a urethane bond, which is a well-known chemical reaction.

[0047] Taking 3-isocyanatepropyltrimethoxysilane as an example, the synthesis route of silane-terminated polyether is as follows:

[0048]

[0049] Another object of the present invention is to provide the use of the silane-terminated polyether prepared from the ethoxyquinoline polymer in the preparation of glass glue, sealant, nail-free glue, and tile adhesive.

[0050] Beneficial effects of the present invention:

[0051] Ethoxyquinoline distillation kettle residue is a chemical solid waste. The invention adopts butyl acetate or xylene to dissolve the ethoxyquinoline distillation kettle residue, extracts organic molecules, filters and removes high-temperature carbides, then carries out aminolysis reaction of the secondary amine functional group of the ethoxyquinoline polymer with propylene oxide, introduces hydroxyl groups, further uses amino alcohol as an initiator, carries out polymerization reaction with propylene oxide under the action of a catalyst to prepare polyether polyol, and the polyether polyol further reacts with an isocyanate-containing organic siloxane to prepare a target product, silane-terminated polyether.

[0052] Due to the introduction of the rigid nitrogen-containing heteroatom quinoline ring structure and the polar carbamate structure, the silane-terminated polyether prepared from the ethoxyquinoline polymer of the present invention cures quickly, and after curing, has the advantages of high strength, strong adhesion, moisture resistance, low odor, environmental protection, and solvent-free. It can be used for glass glue, sealant, nail-free glue, tile adhesive, etc., and can be widely used in the construction industry.

[0053] The invention realizes the resource utilization of the ethoxyquinoline distillation kettle residue, thereby turning waste into treasure. DETAILED DESCRIPTION

[0054] Determination of amine value by perchloric acid-acetic acid titration:

[0055] Weigh about 0.2g (accurate to 0.0001g) of sample, place it in a 250mL conical flask, add about 25mL of glacial acetic acid solution, stir magnetically to fully dissolve, add 2 to 3 drops of crystal violet indicator (dissolve 0.5g crystal violet in 100mL glacial acetic acid), and titrate with the prepared calibrated 0.1mol / L perchloric acid standard solution until the solution changes from purple to pure blue, which is the titration end point. Titrate in parallel two or three times and take the average value [1] .

[0056] The calculation formula of amine value is:

[0057] Where:

[0058] C—concentration of perchloric acid standard solution, mol / L;

[0059] V—volume of perchloric acid standard solution consumed by the sample, mL;

[0060] m—mass of sample, g;

[0061] 56.1—The mass of potassium hydroxide per mole.

[0062] Example 1

[0063] In the first step, 800 g of xylene and 800 g of ethoxyquinoline distillation kettle residue were added to a 2L dissolving kettle, heated to 90° C. with stirring, dissolved for 2 hours, cooled to 40° C. after being uniformly dissolved, filtered with filter paper with a pore size of 20 μm, and black solid particles formed by high-temperature carbonization of organic matter were filtered out to obtain 1515 g of ethoxyquinoline polymer solution. The amine value was determined by perchloric acid-acetic acid titration method and was 93.2 mgKOH / g.

[0064] In the second step, 1203.86 grams of the ethoxyquinoline polymer solution obtained in the first step and 4 grams of lanthanum trifluoromethanesulfonate (CAS No. 52093-26-2) were added to a 5L pressure reactor, stirring was started, the temperature was raised to 110°C, and 127 grams of propylene oxide was added dropwise for reaction. The temperature during the addition was controlled at 110°C to 120°C and the pressure was 0.10 to 0.40 MPa. The addition was completed within 3 hours. After the addition was completed, the temperature was kept at 110°C to 120°C for 2 hours. At this time, the pressure in the reactor dropped to a constant level, and the reactor was cooled to below 50°C to obtain amino alcohol. No separation or purification was required, and the next step of reaction was directly carried out.

[0065] The third step is to drop 20 grams of sodium formate into the 5L pressure reactor, start stirring, heat to 150°C, start dripping 696.96 grams of propylene oxide to react, the dripping process control temperature is 150°C to 155°C, the pressure is 0.10 to 0.40MPa, the dropwise addition is completed within 4 hours, and the dropwise addition is kept at 150°C to 155°C for 3 hours after the dropwise addition. At this time, the pressure in the reactor drops to a constant level, cools to 80°C, starts underpressure distillation to recover xylene to 120°C, and under vacuum degree of -0.098MPa and temperature of 120°C, continues for 10 minutes without distilling out xylene, terminates distillation, cools to 60°C, adds 20 grams of activated clay and stirs for 30 minutes, and then performs circulating filter pressing until clear to obtain 1398 grams of ethoxyquinoline polyether polyols, and recovers 590 grams of xylene.

[0066] In this embodiment, the designed hydroxyl equivalent (the mass number of the compound containing 1 mol of hydroxyl group) of the ethoxyquinoline polyether polyol is 712.76 g / mol, and the measured hydroxyl equivalent is 713.22 g / mol; the conversion relationship between the hydroxyl equivalent and the hydroxyl value is: hydroxyl equivalent = 56.1 × 1000 / hydroxyl value; the hydroxyl value is measured according to the national standard "GB / T 12008.3-2009 Plastic polyether polyols Part 3: Determination of hydroxyl value".

[0067] Step 4: Preparation of silane-terminated polyether: The preparation reaction was carried out under the condition of heating with a thermostatic electric heater. 196 g of 3-isocyanatepropyltrimethoxysilane (CAS No: 15396-00-6, relative molecular weight 205.28), 0.25 g of dibutyltin dilaurate (CAS No.77-58-7) was added to a four-necked flask, and the corresponding stirring device, heating device and temperature control device were connected. The temperature was stirred and raised to 60°C. 713.22 g of the ethoxyquinoline polyether polyol prepared in the third step was added dropwise to the four-necked flask through a constant pressure dropping funnel. The temperature was controlled at 60-65°C during the addition process. The addition was completed within 2 hours. After the addition of the ethoxyquinoline polyether polyol, the temperature was slowly raised to 80°C. The reaction was continued at 80-85°C for 5 hours. When the residual -NCO content of the system was ≤0.1%, it was cooled to 60°C and filtered through a 100-mesh gauze to obtain 892.2 g of silane-terminated polyether (total feed amount 909.92 g).

[0068] Example 2

[0069] raw material:

[0070] Silane-terminated polyether: prepared in Example 1;

[0071] Plasticizer: polypropylene glycol 2000 (DL2000, Jiangsu Litian Technology Co., Ltd. of AJM Group); dioctyl phthalate (DOP, Suzhou Jiading Chemical Technology Co., Ltd.);

[0072] Reinforcing filler: light calcium carbonate, commercially available;

[0073] Thixotropic agent: polyamide wax, commercially available;

[0074] Water absorbent: vinyl tri(β-methoxyethoxy)silane (A-172), Nanjing Xiangqian Chemical Co., Ltd.;

[0075] Coupling agent: γ-glycidyloxypropyltrimethoxysilane (CG-O187), γ-aminopropyltriethoxysilane (CG-A110), Shandong Sike New Materials Co., Ltd.

[0076] Stabilizer: 327, BASF, Germany;

[0077] Catalyst: Dibutyltin dilaurate, Sinopharm Group.

[0078] Preparation of silane terminated polyether sealant:

[0079] Weigh the raw materials according to Table 1, and mix light calcium carbonate (pre-dried), DL 2000, DOP, polyamide wax, vinyl tri(β-methoxyethoxy) silane, Add 327 into a mechanical stirrer, stir at 80 °C in vacuum for 2 h to evenly disperse the raw materials, cool to below 40 °C, add γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane and dibutyltin dilaurate, stir for 0.5 h, discharge the material, and seal it.

[0080] Table 1: Ingredients of silane terminated polyether sealant

[0081]

[0082] Comparative Example 1

[0083] A polyether polyol having the same hydroxyl equivalent as that in Example 1 was designed and prepared, using commonly used glycerol as an initiator and reacting with propylene oxide.

[0084] In a 3L pressure reactor, 92.09 g of glycerol (relative molecular weight 92.09) and 20 g of sodium formate were added, stirring was started, the temperature was raised to 150°C, and 2046.19 g of propylene oxide was added dropwise for reaction. During the addition, the temperature was controlled at 150°C to 155°C and the pressure was 0.10 to 0.40 MPa. The addition was completed within 4 hours. After the addition was completed, the temperature was kept at 150°C to 155°C for 3 hours until the pressure in the reactor dropped to a constant value, the temperature was lowered to 60°C, 10 g of activated clay was added, and stirring was carried out for 30 minutes. Circulation filter pressing was performed to obtain 2095 g of clear and transparent polyether polyol.

[0085] In this comparative example, the designed hydroxyl equivalent (the mass number of the compound containing 1 mol of hydroxyl group) of the polyether polyol is 712.76 g / mol, and the measured hydroxyl equivalent is 713.31 g / mol; wherein, the conversion relationship between the hydroxyl equivalent and the hydroxyl value is hydroxyl equivalent = 56.1 × 1000 / hydroxyl value; the hydroxyl value is measured according to the national standard "GB / T 12008.3-2009 Plastic polyether polyols Part 3: Determination of hydroxyl value".

[0086] Preparation of silane-terminated polyether: The preparation reaction was carried out under the condition of heating with a thermostatic electric heater. 196 g of 3-isocyanatepropyltrimethoxysilane (CAS No: 15396-00-6, relative molecular weight 205.28), 0.25 g of dibutyltin dilaurate (CAS No.77-58-7) was added to a four-necked flask, connected with corresponding stirring device, heating device and temperature control device, stirred and heated to 60°C, 713.31 g of the polyether polyol prepared in this comparative example was added dropwise to the four-necked flask through a constant pressure dropping funnel, the temperature was controlled at 60-65°C during the addition process, and the addition was completed within 2 hours. After the polyether polyol was added dropwise, the temperature was slowly raised to 80°C, and the reaction was continued at a temperature of 80-85°C for 5 hours. When the residual -NCO content of the system was ≤0.1%, it was cooled to 60°C and filtered through a 100-mesh gauze to obtain 892.3 g of silane-terminated polyether (total feed amount of 910.01 g).

[0087] Comparative Example 2

[0088] The silane-terminated polyether prepared in Comparative Example 1 was used to replace the silane-terminated polyether prepared in Example 1, and a sealant was prepared in the same manner as in Example 2, and the performance was tested.

[0089] The performance tests were performed on the sealants prepared in Example 2 and Comparative Example 2.

[0090] Instruments and equipment:

[0091] Shore A hardness tester, model HT-6510, Guangzhou Lantai Instrument Co., Ltd.; universal tensile machine, model LWK-520, Guangzhou Guangcai Testing Instrument Co., Ltd.

[0092] Performance test of silane terminated polyether sealant:

[0093] (1) Determination of surface drying time

[0094] Under standard test conditions (temperature is 23±2℃, relative humidity is 50±5%, the same below), apply the sealant evenly on the glass plate, touch three different parts of the sealant surface with a glass rod every 1 minute until there is no sample adhering to the glass rod, and record the time when it does not stick to the glass rod.

[0095] (2) Determination of curing depth

[0096] Under standard test conditions, squeeze the sealant into a polyethylene cylindrical cup with an inner diameter of 40mm and a depth of about 40mm. Use a blade to trim the sealant surface so that the sealant is flush with the cylindrical cup. Curing for 24 hours, take out the cured layer in the cylindrical cup, and remove the uncured sealant. Use a thickness gauge to measure the film thickness and take the average value.

[0097] (3) Determination of Shore A hardness

[0098] Squeeze the sealant into the corresponding mold, try not to leave bubbles in the glue layer, scrape the surface flush with the edge of the mold, cure it under standard test conditions for 7 days, measure three parts with a Shore A hardness tester and take the average value.

[0099] (4) Tensile strength and elongation at break

[0100] Inject the sealant into the mold and use a scraper to flatten both sides. The thickness of the glue layer is 1.8-2.0mm. Curing under standard conditions for 10 days, take out the film and cut it into corresponding dumbbell-shaped test pieces. Use a universal tensile machine to test the tensile strength and elongation at break.

[0101] (5) Determination of bonding performance

[0102] Referring to GB / T 7124-2008 standard, the surfaces of two substrates with a length of 100 mm and a width of 25 mm were polished with sandpaper, and the stains were wiped off with alcohol, and then glued with sealant to make a lap joint with a bonding area of ​​25 mm × 25 mm and a glue layer thickness of (1.6 ± 0.1) mm. The substrate is an aluminum sheet.

[0103] ① Standard test conditions 1d tensile shear strength

[0104] The prepared overlap sheets were cured for 1 day under standard test conditions and tested on a material tensile machine according to the JC / T 2186-2013 standard of the building materials industry.

[0105] ② 7d tensile shear strength under standard test conditions

[0106] After the prepared overlap sheets were cured for 7 days under standard test conditions, they were tested on a material tensile machine according to the JC / T 2186-2013 standard of the building materials industry.

[0107] Test results:

[0108] Table 2: Performance test results of silane-terminated polyether sealant

[0109] Sealant samples Example 2 Preparation Comparative Example 2 Preparation A commercially available product Surface drying time / min 33 39 35 Curing depth / mm / 24h 3.06 2.78 2.91 Shore A hardness / degree 59 48 57 Tensile strength / MPa 2.21 1.59 2.13 Elongation at break / % 345 320 340 1d tensile shear strength / MPa 1.59 1.55 1.57 7d tensile shear strength / MPa 3.60 2.82 3.54

[0110] The test results are shown in Table 2, which show that the silane-terminated polyether sealant prepared in Example 2 has a 1d tensile shear strength of 1.59 MPa, which meets the standard requirement of 1.5 MPa, and a 7d tensile shear strength of 3.60 MPa, which greatly exceeds the standard requirement of 2.5 MPa. Various properties are superior to those of the silane-terminated polyether sealant prepared in Comparative Example 2, and are not inferior to similar products on the market.

Claims

1. A silane-terminated polyether prepared from an ethoxyquinoline polymer, characterized in that: The preparation method is prepared by the following method: an ethoxyquinoline polymer undergoes an aminolysis reaction with propylene oxide to prepare an amino alcohol; the amino alcohol is used as an initiator to undergo a polymerization reaction with propylene oxide to prepare an ethoxyquinoline polyether polyol; and the ethoxyquinoline polyether polyol reacts with an isocyanate-containing organic siloxane to prepare a silane-terminated polyether.

2. The silane-terminated polyether prepared from the ethoxyquinoline polymer according to claim 1, characterized in that: The ethoxyquinoline polymer is obtained by extraction using the residue of ethoxyquinoline distillation kettle as raw material and one selected from xylene or butyl acetate as extraction solvent.

3. A method for preparing a silane-terminated polyether prepared from the ethoxyquinoline polymer according to claim 1, characterized in that: include: Step (1), pretreatment of ethoxyquinoline still residue: mixing an organic solvent selected from butyl acetate or xylene with the ethoxyquinoline still residue, stirring and heating to 50-100° C., dissolving at 50-100° C. for 1-3 hours, cooling after uniform dissolution, filtering, and obtaining an ethoxyquinoline polymer solution; Step (2), using one selected from butyl acetate or xylene as a reaction solvent, in the presence of a catalyst, the ethoxyquinoline polymer and propylene oxide undergo an aminolysis reaction to prepare an amino alcohol; Step (3), using one selected from butyl acetate or xylene as a reaction solvent and the amino alcohol prepared in step (2) as an initiator, in the presence of a catalyst, the amino alcohol and propylene oxide undergo a polymerization reaction to prepare an ethoxyquinoline polyether polyol; Step (4), in the presence of a catalyst, the ethoxyquinoline polyether polyol prepared in step (3) reacts with an isocyanate-containing organosiloxane, and the terminal hydroxyl group of the ethoxyquinoline polyether polyol reacts with the isocyanate group of the isocyanate-containing organosiloxane to introduce silane, thereby preparing a silane-terminated polyether.

4. The method for preparing a silane-terminated polyether according to claim 3, characterized in that: In step (1), the mass ratio of the butyl acetate or xylene to the ethoxyquinoline distillation kettle residue is 1:0.5 to 1:2.0, preferably 1:1.0 to 1:1.

6.

5. The method for preparing a silane-terminated polyether according to claim 3, characterized in that: In step (1), the amine value of the ethoxyquinoline polymer solution is usually 80 to 110 mgKOH / g.

6. The method for preparing a silane-terminated polyether according to claim 3, characterized in that: In step (2), the mass ratio of the ethoxyquinoline polymer solution to propylene oxide is (56.1×1000 / Av):[58.08×(1.0-1.1)]; wherein Av is the amine value of the ethoxyquinoline polymer solution; The catalyst is at least one of lanthanum trifluoromethanesulfonate, neodymium trifluoromethanesulfonate, erbium trifluoromethanesulfonate, ytterbium trifluoromethanesulfonate, scandium trifluoromethanesulfonate, cerium trifluoromethanesulfonate, stannous trifluoromethanesulfonate, and bismuth trifluoromethanesulfonate, preferably at least one of lanthanum trifluoromethanesulfonate, ytterbium trifluoromethanesulfonate, and scandium trifluoromethanesulfonate; The amount of the catalyst is 0.1wt% to 1wt% of the total mass of the ethoxyquinoline polymer solution and propylene oxide; The temperature of the aminolysis reaction is 80° C. to 120° C., and the pressure is 0.1 to 0.4 MPa.

7. The method for preparing a silane-terminated polyether according to claim 3, characterized in that: In step (3), the mass ratio of the ethoxyquinoline polymer solution to propylene oxide is (56.1×1000 / Av):[58.08×(1.0~50)], preferably (56.1×1000 / Av):[58.08×(3~40)], and more preferably (56.1×1000 / Av):[58.08×(3~6)]; wherein Av is the amine value of the ethoxyquinoline polymer solution; The catalyst is at least one of sodium formate, potassium formate, sodium benzoate and potassium benzoate; the amount of the catalyst is 1wt% to 5wt% of the total mass of the amino alcohol and propylene oxide; The polymerization reaction temperature is 100°C to 165°C, preferably 140°C to 155°C, the polymerization reaction pressure is 0.1 to 0.6 MPa, preferably 0.1 to 0.4 MPa, and the polymerization reaction time is 1 to 8 hours, preferably 3 to 7 hours.

8. The method for preparing a silane-terminated polyether according to claim 3, characterized in that: In step (4), the mass ratio of the ethoxyquinoline polyether polyol to the isocyanate-containing organosiloxane is (56.1×1000 / V OH ):[(0.5~1.0)×M], preferably (56.1×1000 / V OH ):[(0.8~1.0)×M]; Among them, V OH is the hydroxyl value measured for the ethoxyquinoline polyether polyol, and M is the relative molecular weight of the organosiloxane containing an isocyanate group; The amount of the catalyst is 100 to 3000 ppm, preferably 100 to 1000 ppm, of the total mass of the ethoxyquinoline polyether polyol and the isocyanate-containing organosiloxane; In step (4), the reaction temperature is 50°C to 95°C, preferably 60°C to 85°C, and the reaction time is 1 to 6 hours.

9. The method for preparing a silane-terminated polyether according to claim 3 or 8, characterized in that: In step (4), the organosiloxane is 3-isocyanate propyl trimethoxy silane or 3-isocyanate propyl triethoxy silane, preferably 3-isocyanate propyl trimethoxy silane; The catalyst is dibutyltin dilaurate.

10. Use of the silane-terminated polyether according to claim 1 or 2 in the preparation of glass glue, sealant, nail-free glue and tile adhesive.

Citation Information

Patent Citations

  • Tire

    CA120386A

  • Machanism for transmitting powet to dynamo machines

    CA77587A